Transient simulation of a two-door frost-free refrigerator subjected to periodic door opening and evaporator frosting - Borges, Bruno N.; Melo, Cláudio; Hermes, Christian J.L. (Applied energy, 2015)
•Transient behavior of a refrigerator under periodic door opening is simulated.•The refrigeration loop is modeled following a semi-empirical quasi-steady approach.•Energy and moisture transfer into and within the compartments are modeled.•Key heat and mass transfer parameters were derived from in-house experiments.•Predictions followed closely the experimental trends for power and temperatures. This paper describes a quasi-steady-state simulation model for predicting the transient behavior of a two-door household refrigerator subjected to periodic door opening and evaporator frosting. A semi-empirical steady-state model was developed for the refrigeration loop, whereas a transient model was devised to predict the energy and mass transfer into and within the refrigerated compartments, and also the frost build-up on the evaporator. The key empirical heat and mass transfer parameters required by the model were derived from a set of experiments performed in-house in a climate-controlled chamber. In general, it was found that the model predictions followed closely the experimental trends for the power consumption (deviations within ±10%) and for the compartment temperatures (deviations within ±2K) when the doors are opened periodically and frost is allowed to accumulate over the evaporator.